Investigation about factores related to evasion in distance education courses from tutors point of view (Research, Society and Development, 2020)
Distance education has been growing steeply across the globe, of course, such growth has been accompanied by many problems and challenges. Therefore, this study aimed to investigate some factors that may be related to dropout in Accounting and Administration courses in a private Uviversity in Pernambuco state (Brazil) from the perspective of tutors who work in these respective courses. The methodology used was exploratory research using a semi-structured questionnaire applied to 13 tutors from the mentioned courses, characterizing the research as a case study. The results showed that among the factors that were most related to dropout in distance learning courses, from the point of view of tutors, were: lack of time for the student to dedicate to distance learning activities, financial difficulties and personal problems. More studies are needed to better understand which factors most explain dropout in distance learning courses.